Are sociodemographic characteristics associated with spatial variation in the incidence of OHCA and bystander CPR rates? A population-based observational study in Victoria, Australia. Issue 11 (7th November 2016) - Straney, Lahn D; Bray, Janet E; Beck, Ben; Bernard, Stephen; Lijovic, Marijana; Smith, Karen
Abstract : Background: Rates of out-of-hospital cardiac arrest (OHCA) and bystander cardiopulmonary resuscitation (CPR) have been shown to vary considerably in Victoria. We examined the extent to which this variation could be explained by the sociodemographic and population health characteristics of the region. Methods: Using the Victorian Ambulance Cardiac Arrest Registry, we extracted OHCA cases occurring between 2011 and 2013. We restricted the calculation of bystander CPR rates to those arrests that were witnessed by a bystander. To estimate the level of variation between Victorian local government areas (LGAs), we used a two-stage modelling approach using random-effects modelling. Results: Between 2011 and 2013, there were 15 830 adult OHCA in Victoria. Incidence rates varied across the state between 41.9 to 104.0 cases/100 000 population. The proportion of the population over 65, socioeconomic status, smoking prevalence and education level were significant predictors of incidence in the multivariable model, explaining 93.9% of the variation in incidence among LGAs. Estimates of bystander CPR rates for bystander witnessed arrests varied from 62.7% to 73.2%. Only population density was a significant predictor of rates in a multivariable model, explaining 73% of the variation in the odds of receiving bystander CPR among LGAs. Conclusions: Our results show that the regional characteristics which underlie the variation seen in rates of bystander CPR may be region specific and may require study in smaller areas. However, characteristics associated with high incidence and low bystander CPR rates can be identified and will help to target regions and inform local interventions to increase bystander CPR rates.